A CFD Modeling Coupled with VOF Method and Solidification Model for Molten Jet Breakup at Low Velocity. (4th March 2023) - Liu, Tao; Zhou, Yuan; Zhong, Mingjun; Gong, Houjun
Abstract: In a reactor severe accident, molten jet breakup and solidification are important behaviors after large pours of molten material fall into the coolant in-vessel or ex-vessel. However, heat and mass transfer processes inside melt during jet breakup have not been studied sufficiently. Existing research on jet fragmentation is relatively macroscopic, and the micro interface condensation details are not well studied. In this paper, a two-dimensional multiphase computational fluid dynamics (CFD) code with the Volume of Fluid (VOF) method and solidification model is applied to simulate molten jet breakup with surface solidification. The VOF model is used to capture the interface, study the details, and add the influence of solidification. Solidification and instability can be seen at the interface. In order to simulate melt solidification, an energy equation is modeled using an enthalpy-based formulation, and viscosity variation during phase change is taken into account. The comparative results between the CFD code and jet breakup experiments show that melt jet front position histories, breakup length, and breakup time are in good agreement with the experiments. The simulation results show that crust formation of the jet surface suppresses surface instability and jet breakup behavior. As the interfacial temperature decreases, the droplet cumulative mass fraction decreases, and the solidified metal proportion increases. The simulation results by the CFD code with the solidification model are valuable and important for understanding the molten jet breakup mechanism.